Efficacy and safety of atezolizumab–bevacizumab vs pembrolizumab-lenvatinib in unresectable hepatocellular carcinoma: a retrospective, cohort study - Hu, Zili; Yang, Zhoutian; Fu, Zibo; Fu, Yizhen; Ma, Zeliang; Zhou, Zhongguo; Chen, Minshan; Zhang, Yaojun (Frontiers in Immunology, 2024)
BackgroundThe relative superiority of atezolizumab–bevacizumab versus pembrolizumab-lenvatinib in treatment of unresectable hepatocellular carcinoma (HCC) remains uncertain. This study aims to compare the efficacy of atezolizumab–bevacizumab and pembrolizumab-lenvatinib in first-line treatments for unresectable HCC.MethodsA total of 72 patients receiving pembrolizumab-lenvatinib (PL group) and 92 patients receiving atezolizumab-bevacizumab (AB group) between January 2019 and June 2023 were included in this study. By employing propensity score matching (PSM), we compared the overall survival (OS) and progression-free survival (PFS) between the two groups.ResultsAfter PSM, the 1-, 2-, and 3-year OS rates were 70.4%, 54.5%, and 40.0% in the PL group, and 88.4%, 44.2%, and 44.2% in the AB group, respectively. The 6-, 12-, and 18-month PFS rates were 56.9%, 43.0%, and 32.1% in the PL group, and 74.2%, 40.9%, and 30.7% in the AB group, respectively. No significant differences were observed in both OS (HR, 0.498; 95% CI, 0.217-1.143; P = 0.1) and PFS (HR, 0.913; 95% CI, 0.512-0.1.629; P = 0.758) between the two groups. Through subgroup analysis, we developed a Cirrhosis-Portal vein invasion-ALBI (CPA) score and identified that the AB group exhibited significantly longer OS than the PL group in the CPA high population (HR, 0.219; 95% CI, 0.075–0.637; P = 0.005). The treatment-related adverse events between the PL group and the AB group were comparable.ConclusionsThis study suggests that the efficacy of pembrolizumab-lenvatinib and atezolizumab-bevacizumab is comparable in first-line treatment of unresectable HCC, the atezolizumab-bevacizumab combination may confer additional benefits for patients with high CPA scores compared to pembrolizumab-lenvatinib.